Effect of chemomechanical caries removal on bonding of resin‐modified glass ionomer cement adhesives to caries‐affected dentine. (19th May 2015) - Hamama, HHH; Yiu, CKY; Burrow, MF
Abstract: Background: This study evaluated the effect of: (1) chemomechanical caries removal (CMCR); (2) dentine surface treatments and (3) dentine substrates on adhesion of resin‐modified glass ionomer cement (RMGIC) adhesives. Methods: One hundred and twenty permanent molars exhibiting moderate cavitation on the occlusal surface into dentine were used. Seventy‐five carious molars were used for bond strength testing; the remaining 45 for micromorphological evaluation of the bonded interface. Caries was excavated with NaOCl‐based CMCR (Carisolv), enzyme‐based CMCR (Papacarie), or conventional rotary caries removal methods. Dentine surface treatment was performed using 37% phosphoric acid, 25–30% PAA or 20% PAA + 3% AlCl3 . Results: Three‐way ANOVA revealed that all three factors 'caries removal methods', 'dentine surface treatments' and 'dentine substrates' did not significantly affect bond strength (p > 0.05). Scanning electron microscopy micrographs showed that the acid‐base resistant layer was thicker in caries‐affected dentine compared to sound dentine. Conclusions: NaOCl‐ and enzyme‐based CMCR methods have no adverse effect on adhesion of RMGIC adhesives to sound and caries‐affected dentine. Dentine surface treatment with 37% phosphoric acid for 5 s has no negative effect on bonding of RMGIC adhesives to dentine compared with using polyacrylic acid for 10 s. RMGIC adhesives bonded well to both sound and caries‐affected dentine.